Prognostic relevance of persistence of myelin oligodendrocyte glycoprotein antibody in pediatric acute disseminated encephalomyelitis - Banerjee, Asish; Mitra, Meenakshi (Asian Journal of Medical Sciences, 2022)
Background: Myelin oligodendrocyte glycoprotein (MOG) antibody plays a significant role in demyelination in pediatric acute disseminated encephalomyelitis (ADEM). Aims and Objectives: To assess the prognostic relevance of persistence of MOG antibody in pediatric ADEM. Materials and Methods: A prospective observational study was conducted over a period of 3 years. Data were collected from Department of Pediatrics of a tertiary care hospital in Durgapur. Neurological examination findings, magnetic resonance imaging brain and spinal cord, electroencephalogram findings, and MOG antibody titer were noted. All patients were followed up for 1 year. MOG Antibody titer was repeated after 6 months of the first episode of demyelination. Data gathered from the patients was documented. Data analysis was performed using fisher’s exact test on graph pad 2×2 contingency table. P<0.05 was considered as statistically significant. Results: Fifty-three children were diagnosed with ADEM. Among these, 27 children were MOG antibody-positive (51%). One child expired and five children were lost to follow up. Forty-seven children were followed up for 1 year. MOG antibody titer was sent at the time of diagnosis and 6 months after first episode of demyelination. Persistently positive MOG antibody (positive at 6 months after 1st episode of demyelination) was significantly associated with the development of multiphasic disseminated encephalomyelitis (MDEM) (P<0.0001), epilepsy (P=0.0176), steroid dependency (P<0.0001), persistent gait disturbance (P=0.0026), but not with the development of Multiple Sclerosis (P=1.000). Conclusion: Persistently positive MOG Antibody was significantly associated with development of MDEM, epilepsy, persistent gait disturbance, and steroid dependency.